Effect of the compaction platform on the densification parameters of tableting excipients with different deformation mechanisms (2014)
ABSTRACT: Several compaction models have been attempted to explain the compression and compaction phenomena of excipients. However, the resulting parameters could be influenced by the compaction platform such as dwell time, compact mass, geometry and type of material. The goal of this study is to assess the effect of these variables on the densification parameters obtained from key models such as Heckel, non-linear Heckel, Kawakita, Carstensen, and Leuenberger. The relationship among the parameters derived was determined by employing a Principal Component Analysis. Results indicated that factors such as compact geometry, consolidation time and compact mass had a negligible impact on parameters such as tensile strength, yield pressure and compressibility. On the contrary, the excipient type had the largest influence on these parameters. Further, the Leuenberger (γ) and Carstensen (f) parameters were highly correlated and related to the excipient deformation mechanism. Sorbitol and PVP-k30 were the most highly compactable excipients and were characterized for having a low yield pressure (Py), compressibility (a), and critical porosity (εc). The magnitude of these parameters was highly dependent on the consolidation behavior of each material.